Dynamic Evolution of Magnetic Flux Ropes in Active Region 11429. II. Magnetic Characteristic of the Footpoints During the Preeruption and Eruption Phases - Yin Zhang; Jing Huang; Jihong Liu; Shangbin Yang; Yunfei Yang; Baolin Tan (The Astrophysical Journal)
Magnetic flux rope (MFRs) are the most probable core structure of coronal mass ejections (CMEs). Their footpoints on the photosphere are the only feature for which their magnetic properties can be accurately measured, and to some extent, determine the property of the whole MFR. So far, the magnetic properties of footpoints are still a mystery. Y. Zhang et al. presented the dynamic evolution of four MFRs involved in a major eruption. For this special event, the footpoints of the MFRs could be identified by extreme-ultraviolet (EUV) brightening and MFR morphology during the preeruption phase, and by conjunction, EUV dimming during the eruption phase. This is a new effort to identify the footpoints of MFRs during the preeruption phase. This identification discloses that all footpoints originate out of the umbra and penumbra of the sunspots. The footpoint areas and magnetic flux during the preeruption phase are about 10 ^7 km ^2 and around the order of 10 ^19 –10 ^20 Mx, respectively. During the eruption phase, the footpoint area and the magnetic flux are about 10 ^8 km ^2 and around the order of 10 ^20 Mx, respectively. The temporal evolution of the magnetic features around the footpoints disclose that all footpoint pairs belong to nonconjugated opposite polarities. This observational evidence will help us to understand the magnetic nature of MFRs and their associated CMEs.